2012
DOI: 10.1593/neo.121192
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcriptional Corepressor CtBP1 in Prostate Cancer Progression

Abstract: Transcriptional repressors and corepressors play a critical role in cellular homeostasis and are frequently altered in cancer. C-terminal binding protein 1 (CtBP1), a transcriptional corepressor that regulates the expression of tumor suppressors and genes involved in cell death, is known to play a role in multiple cancers. In this study, we observed the overexpression and mislocalization of CtBP1 in metastatic prostate cancer and demonstrated the functional significance of CtBP1 in prostate cancer progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 35 publications
4
84
0
Order By: Relevance
“…Our data also showed that restoration of miR-188-5p can promote PC-3 cells' sensitivity to adriamycin via the suppression of LAPTM4B. Previous study demonstrated that LAPTM4B can motivate multidrug resistance of cancer cells by promoting drug efflux and anti-apoptosis by activating PI3K/AKT signaling [15,16,32]. Collectively, these results indicated that restoration of miR-188-5p suppressed PI3K/AKT signaling pathway by targeting LAPTM4B.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our data also showed that restoration of miR-188-5p can promote PC-3 cells' sensitivity to adriamycin via the suppression of LAPTM4B. Previous study demonstrated that LAPTM4B can motivate multidrug resistance of cancer cells by promoting drug efflux and anti-apoptosis by activating PI3K/AKT signaling [15,16,32]. Collectively, these results indicated that restoration of miR-188-5p suppressed PI3K/AKT signaling pathway by targeting LAPTM4B.…”
Section: Discussionsupporting
confidence: 72%
“…Proliferation and metastasis, two hallmarks of malignancy, are the leading causes for the cancer-related death [32,33]. Ectopic miR-188-5p expression significantly repressed the proliferation, migration and invasion of PC-3 and LNCaP cells in vitro , and tumour growth and metastasis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression and mislocalization of CtBP is evident in prostate cancer cells. Furthermore, knockdown of CtBP in prostate cancer cell lines inhibited cell invasion (140). In melanoma, CtBPs are shown to repress BRCA1 and p16INK4a (141).…”
Section: Other Regulators Of Ctbp In Cancermentioning
confidence: 98%
“…3A shows that CTBP1, a well-recognized EMT regulator [18], was up-regulated in endometrial carcinoma cells following BTR treatment. To confirm whether CTBP1 is involved in BTR-induced EMT, we suppressed endogenous CTBP1 levels using CTBP1-siRNA [27]. Western blotting showed that the expression level of CTBP1 was significantly inhibited by CTBP1-siRNA, and the BTR-induced up-regulation of N-cadherin/Vimentin and down-regulation of E-cadherin were reversed by CTBP1-siRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%